Aspirations and Inequality - Genicot, Garance; Ray, Debraj (Econometrica, 2017)
This paper develops a theory in which society-wide economic outcomes shape individual aspira-tions, which affect the investment incentives of individuals. Through its impact on investments, aspirations in turn affect ambient social outcomes. We explore this two-way link. A central feature is that aspirations that are moderately above an individual’s current standard of living tend to encourage investment, while still higher aspirations may lead to frustration and lower investment. When integrated with the feedback effect from investment, we are led to a the-ory in which aspirations and income evolve jointly, and the social determinants of preferences play an important role. We examine conditions under which growth is compatible with long-run equality in the distribution of income. More generally, we describe steady state income distri-butions, which are typically clustered around local poles. Finally, the theory has predictions for the growth rates along the cross-section of income. We use these predictions to calibrate the model so that it fits growth data by income percentile for 43 countries, and back out the implicit aspirations-formation process that underlies these observations.